2008
DOI: 10.1007/s00455-007-9142-z
|View full text |Cite
|
Sign up to set email alerts
|

Standard Values of Maximum Tongue Pressure Taken Using Newly Developed Disposable Tongue Pressure Measurement Device

Abstract: It is clinically important to evaluate tongue function in terms of rehabilitation of swallowing and eating ability. We have developed a disposable tongue pressure measurement device designed for clinical use. In this study we used this device to determine standard values of maximum tongue pressure in adult Japanese. Eight hundred fifty-three subjects (408 male, 445 female; 20-79 years) were selected for this study. All participants had no history of dysphagia and maintained occlusal contact in the premolar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
292
8
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(360 citation statements)
references
References 18 publications
35
292
8
6
Order By: Relevance
“…The maximum tongue pressure in females had the highest value at Stage III B. Utanohara et al (2008) reported that the mean maximum tongue pressure was around 35 kPa among Japanese females aged 20–30 years. In this study, the mean maximum tongue pressure in Stage VA females was 30.503 kPa, although that in Stage III B females was 36.877 kPa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The maximum tongue pressure in females had the highest value at Stage III B. Utanohara et al (2008) reported that the mean maximum tongue pressure was around 35 kPa among Japanese females aged 20–30 years. In this study, the mean maximum tongue pressure in Stage VA females was 30.503 kPa, although that in Stage III B females was 36.877 kPa.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies showed that maximum tongue pressure remained constant from 20s to 60s and started to decrease from the 70s in females (Utanohara et al, 2008; Vanderwegen et al, 2013). We suggest that females need training with respect to tongue pressure, by the mixed dentition stage, to increase the peak of tongue pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups (Nicosia et al, 2000;Youmans and Stierwalt, 2006) reported previously similar figures and highlighted also that pressure varies along the tongue position and is higher at the back. The mean peak tongue pressure 20 was also found to remain similar across different age groups, although maximum tongue strength was found to decrease with age (Youmans and Stierwalt, 2006;Utanohara et al, 2008). Clavé et al (2006) showed that brain damage or neurodegenerative conditions result in decreased tongue pressure, decreased bolus kinetic energy and increased transit time.…”
mentioning
confidence: 90%
“…Bulbos preenchidos por ar são difíceis de serem ajustados devido a estes escorregarem facilmente na superfície da língua e o tubo conector não ter marcações para indicar a posição do mesmo depois do fechamento dos lábios. Além disso, este tipo de instrumento deveria conter um sistema de pressurização como proposto na literatura 25 , para manter o bulbo inflado com ar à mesma pressão antes de cada medição.…”
Section: Figura 4 -Dispositivos Que Empregam Outras Tecnologiasunclassified